Is There an Association between Symptoms of Anxiety and Depression and Quality of Life in Patients with Chronic Obstructive Pulmonary Disease? - Verônica F Parreira; Renata N Kirkwood; Megan Towns; Isabel Aganon; Lauren Barrett; Catherine Darling; Michelle Lee; Kylie Hill; Roger S Goldstein; Dina Brooks (Canadian Respiratory Journal)
BACKGROUND: In addition to symptoms, such as dyspnea and fatigue, patients with chronic obstructive pulmonary disease (COPD) also experience mood disturbances.